Microvascular Density Analysis of Patients with Trigeminal Herpes Zoster—An Optical Coherence Tomography Angiography Study - Eliane Luisa Esser; Steven Brozmann; Sebastian Dierse; Martin Dominik Leclaire; Nicole Eter; Nataša Mihailovic; Jan Ehrchen (Biomedicines)
Purpose: Varicella zoster virus (VZV) vasculopathy can occur in patients with herpes zoster (HZ). Our aim was to evaluate the retinal microvascular vessel density (VD) in patients with trigeminal HZ measured by optical coherence tomography angiography (OCTA). Methods: 48 eyes of 24 patients with HZ and 48 eyes of 24 healthy age- and gender-matched controls were included in this study. All participants underwent an OCTA examination using RTVue XR Avanti with AngioVue. The VD data of the macular 3 × 3 mm OCT angiogram of the superficial capillary plexus (SCP), the deep capillary plexus (DCP), and the choriocapillaris (CC) as well as the VD data of the optic nerve head (ONH) were extracted and analyzed. Results: The VD in the SCP, DCP, and CC of patients with HZ was significantly lower compared with healthy controls (p < 0.05). Equally, there was a noticeable reduction in the inside disk area of the ONH. There was no statistically noticeable reduction in the FAZ area and central retinal thickness. Conclusions: In this study, HZ patients demonstrated a decrease in the retinal VD of the SCP, DCP, ONH, and the CC. Quantitative analysis of retinal perfusion using OCTA may therefore help in the diagnosis and monitoring of HZ. Further studies must show to what extent this may be an indication of VZV-related vasculopathy and whether OCTA data can be used as a biomarker in these patients in the future.